2013
DOI: 10.4161/psb.22999
|View full text |Cite
|
Sign up to set email alerts
|

Cell autonomous and non-cell autonomous control of rhizobial and mycorrhizal infection inMedicago truncatula

Abstract: These authors contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Myc-LCOs, and DMI3, are also likely to control calcium spiking during mycorrhization (Sieberer et al, 2012;Rival et al, 2013), and Myc-LCOs are proposed to trigger a regulatory mechanism to prevent over-colonization of roots by AM fungi (Lauressergues et al, 2012).…”
Section: Major Responses To Myc-lcos Indicate Important Roles In Cellmentioning
confidence: 99%
“…Myc-LCOs, and DMI3, are also likely to control calcium spiking during mycorrhization (Sieberer et al, 2012;Rival et al, 2013), and Myc-LCOs are proposed to trigger a regulatory mechanism to prevent over-colonization of roots by AM fungi (Lauressergues et al, 2012).…”
Section: Major Responses To Myc-lcos Indicate Important Roles In Cellmentioning
confidence: 99%
“…Initiation of eIT is specifically targeted by AOI in agreement with previous evidence that eIT and cIT formation are under different genetic control (Miri et al ., ) and are mediated by cell‐autonomous mechanisms (Rival et al ., ). Altogether these findings indicate that IT formation is a highly controlled process to which different mechanisms contribute.…”
Section: Discussionmentioning
confidence: 97%
“…It was found that root secretions produced relatively more accumulated Nod factors during the early stages of plant growth (early AMF infestation) and relatively less of such signaling substances during later AMF infestation [ 195 ]. AMF may secrete a certain amount of Myc factor at the early stage of infestation to inhibit the accumulation of Rhizobium to the host plant, while the signaling substances produced at the middle stage of infestation changed and the antagonistic effect gradually decreased, showing a progressive synergistic effect on rhizobium [ 196 ]. Although inoculation with AMF showed negative tropism to Rhizobium at the early stage of symbiosis formation, and the two had some antagonistic effects [ 197 ].…”
Section: Plant-amf-rhizobium Work Together To Regulate Metal Homeostasismentioning
confidence: 99%